Inside Back Cover: Cover Image, Volume 21, Issue 2. Issue 2 (21st March 2022) - Ye, Jianming; Guo, Jiaqing; Li, Tairan; Tian, Jiaxin; Yu, Mengxi; Wang, Xiaochen; Majeed, Usman; Song, Wei; Xiao, Jianbo; Luo, Yane; Yue, Tianli
Abstract : The cover image is based on the Original Article Phage?based technologies for highly sensitive luminescent detection of foodborne pathogens and microbial toxins: A review by Yane Luo et al., https://doi.org/10.1111/1541-4337.12908 .